Psychological characteristics of developing excellence in mixed martial arts athletes - Ruiz Barquín, Roberto; Gutiérrez García, Carlos; Plura Maldonado, Adrián (Revista de Artes Marciales Asiáticas, 2019)
The aim of this study was to describe the perception of sports talent and excellence development in a sample of MMA fighters, and compare the obtained results with those of previous studies. A total of 42 adult (male and female) MMA athletes of several levels (amateur, semi-professional and professional) participated in the study. A socio-demographic questionnaire and the Psychological Characteristics of Developing Excellence Questionnaire – PCDEQ were used for collecting data. Statistical analyses included descriptive statistics and student’s t-test for means comparison. In general, MMA athletes obtained higher scores than those reported by samples of other sports in previous studies, and more specifically in factors I - Support for long-term success, II - Imagery use during practice and competition, and IV - Ability to organise and engage in quality practice. This can be explained due to the higher average age of our sample and the professional or semi-professional level already achieved by many of the MMA fighters. The study also revealed that MMA fighters may need specific psychological training related to factor III - Coping with performance and developmental pressures.